The Rhythm of Prose Axel Bakunts’s - Jrbashyan, Ashkhen (Bulletin of Yerevan University B: Philology, 2023)
The article attempts to analyze the elements of rhythm in the prose of Aksel Bakunts, to show that rhythm dissolves in all elements of a prose work - in the nature of plot, compositional structure, dialogues, in the parallelism of artistic images. At the same time, Bakunts' prose is considered in the context of the so-called "ornamental" prose in Russian literature of the early 20th century, as an Armenian response to the artistic changes of that time, as a kind of convergence of the principles of prose and verse. All this significantly expanded the possibilities of artistic expression in Armenian literature and opened a new path for the further development of Armenian prose.
Keywords: prose rhythm; meter; ornamental prose; lyricism; artistic image; internal rhythm; composition; fragmentary plot; parallelism